Europejska reklama i towarzysząca jej nienawiść - Grochowski, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper concerns the rarely discussed subject of hate speech in advertising messages. Hate speech is primarily related to the issue of freedom of speech, which, however, is not absolute freedom. The scope of freedom of speech involves audiovisual statements and other forms of expression that may incite hatred, discrimination and violence against other groups. ECRI general recommendation no. 1 classifies such behaviors as criminal offences. Such statements acquire legal and penal status, provided that a certain act has been committed intentionally – dolus directus coloratus. Advertising discourse frequently forces us to treat others in an ignoble manner thus becoming a stimulus to violence.